Методика визначення повних втрат в соплових решітках турбомашин - Лапузін, Олександр Вікторович; Суботович, Валерій Петрович; Юдін, Юрій Олексійович; Науменко, Світлана Петрівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
Для оцінки рівня аеродинамічної ефективності соплових решіток парових і газових турбін запропонований метод, в якому замість коефіцієнта втрат кінетичної енергії визначається коефіцієнт повних втрат, який враховує як втрати кінетичної енергії так і кінематичні втрати. Цей метод перетворює вихідний нерівномірний просторовий потік за решіткою у вісесиметричний циліндричний. В протестованій кільцевій решітці з циліндричними меридіональними границями коефіцієнт повних втрат приблизно на 0,02 перевищує коефіцієнт втрат кінетичної енергії. Врахування кінематичних втрат при виконанні теплових розрахунків турбін відкидає необхідність не зовсім обґрунтованого корегування коефіцієнта втрат кінетичної енергії соплової решітки на 0,01 –0,03, що підвищує точність розрахунків.

To assess the level of aerodynamic efficiency of the nozzle cascades of steam and gas turbines, the method was suggested to determine the total loss coefficient instead of kinetic energy loss coefficient that takes into account both kinetic energy losses and kinematic losses. This method allows us to transform the original non-uniform spatial flow behind the cascade into an axisymmetric cylindrical flow. In the tested annular cascade with cylindrical meridional boundaries, the total loss coefficient is approximately 0.02 higher than the kinetic energy loss coefficient. By taking into account kinematic losses when performing thermal calculations for the turbines we eliminate the need for an unjustified correction of the kinetic energy loss coefficient of the nozzle cascade by 0.01 –0.03, increasing thus the accuracy of calculations. To analyze the operation of individual sections of the nozzle cascade and to determine the relationship between kinetic energy losses and kinematic losses, it is advisable to use the averaging method proposed in 2021 that enables the transformation of the initial non-uniform spatial flow behind the cascade into an axisymmetric conical flow. The aerodynamic characteristics of this flow are the widely used kinetic energy loss factor and two averaged flow angles.
The method of determining total losses in the nozzle cascades of turbomachines
Keywords: соплова решітка; кінематика потоку; методи усереднення параметрів; коефіцієнти втрат; nozzle cascade; flow kinematics; parameter averaging methods; loss coefficients